Kinetic Study of Esterification of Free Fatty Acid in Low Grade Crude Palm Oil using Sulfuric Acid - Satriana Satriana; Muhammad Dani Supardan (Department of Chemical Engineering, Universitas Gadjah Mada, 2008)
The kinetics of the esterification of free fatty acids (FFA) in low grade crude palm oil (CPO) with methanol was studied. In this work, the effects of operational variables involved in the esterification process i.e. alcohol to oil molar ratio, reaction temperature, agitation speed and the initial amount of FFA of oil, were studied in the presence of sulphuric acid as catalyst at concentration of 1%-w. The experimental results show that the esterification process could lead to a practical and cost effective FFA removal unit in front of typical oil transesterification for biodiesel production. The experimental results were found to fit a first-order kinetic law. The influence of temperature on the kinetic constants was determined by fitting the results to the Arrhenius equation.